Tinjauan Yuridis Tindak Pidana Pemalsuan Dokumen Untuk Pencairan Asuransi Kecelakaan (Studi Putusan Nomor: 2893/Pid.B/2020/PN.Mdn) - Simarsoit, Edward Armando; Mubarak, Ridho (Universitas Medan Area, 2025)
The crime of document forgery is a criminal offense that has implications for the truth and trustworthiness of individuals. Perpetrators use document forgery to gain personal benefit. A common type of document forgery is the falsification of insurance policy data. An insurance policy is a consensual insurance or coverage agreement that must be made in writing in a deed between the parties to the agreement. Decision Number: 2893/Pid.B/2020/PN.Mdn reflects fairness, certainty, and benefit. The Panel of Judges' assessment of the more appropriate charge to apply to the defendant is an alternative charge, so that the Panel of Judges, taking into account the legal facts, chose to consider the first, second, and third charges of violating Article 220 of the Criminal Code.